Characteristics of communication between dentists and their assistants - Barsevičienė, Šarūnė; Paulauskienė, Viktorija; Holland, Kristina (Slauga. Mokslas ir praktika, 2023)
Summary. Effective teamwork requires communication and cooperation among team members, exchange of various knowledge, information [1]. Communication skills (both verbal and non-verbal) of dentists and their assistants with a patient, colleague or other healthcare professional are considered the basis of their professionalism [2].Research aim – is to reveal the peculiarities of professional communication between dentists and their assistants.Research methods: qualitative research - semi-structured interview method and content analysis.Research results and conclusions. During the research it was established that effective communication between dentists and their assistants leads to good work results and work productivity. Poor communication leads to communicational problems and miscommunication. Based on the results of the theoretical analysis and empirical research conducted in the study, the model of communication between dentists and their assistants reveals that in order to achieve effective communication, dentists must recognize the importance of the professional role of their assistants, be tolerant, and dentists' assistants must strengthen their professional role and be able to adapt. It is also very important that both dentists and their assistants understand the importance of effective communication and that effective communication means not only sharing information, but also establishing good interpersonal relationships.
Keywords: professional communication; cooperation; relations